The Women's Philanthopic Movement During The Covid-19 Pendemic: - Napsiah; Yayan Suryana (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
The purpose of this study is to prove that stereotypes about women are gentle and protective, and irrational because they are only suitable in the domestic sector and are not worthy of being driving actors in the field of philanthropy. However, these stereotypes do not always have a negative impact, but under certain conditions they actually raise concern for vulnerable groups in the era covid-19 pandemic. This can be proven in the women's movement, the community of Kartini UIN SUKA, a community engaged in education and the Fetus and womb community which is engaged in mental health by direct interviews and using content analysis on the Fetus and Womb community Instragram which is strengthened, supported by observations and data from journals and websites. This study concludes that, during the Covid-19 pandemic, with limited space and movement due to the WFH policy, women formed a community engaged in philanthropy as a form of concern for others affected by Covid-19. Providing assistance to students in the form of groceries and educating women on mental health through virtual space is a movement that is urgently needed during the Covid-19 pandemic. This movement is not only beneficial to recipients but is also able to provide a stimulus to other groups to be motivated to foster a diverse attitude towards others even in limited circumstances. The act of driving philanthropy as well as being an actor of change is a way to break through patriarchal culture.